Dr. Nadzirah creates MD-SOLARES: Solar Assisted Membrane Distillation System - Nur Hartini, Mohd Hatta (UMPSA, 2024)
GAMBANG, 1 January 2024 – MD-SOLARES or known as Membrane Distillation Equipped with Solar Energy System is a solar-assisted membrane distillation system created to solve the problem of difficulty in obtaining clean water supply in island and inland areas.